2021
DOI: 10.1111/jvh.13551
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus–induced hepatocarcinogenesis: A virological and oncological perspective

Abstract: Hepatitis B virus (HBV) is a partially double-stranded DNA virus associated with hepatocellular carcinoma (HCC). The viral integration into the hepatocyte genome, the viral protein-induced oncogenesis, the increased hepatocyte turnover and the chronic inflammatory response towards HBV are all hypothesized mechanisms for the development of HCC. The fact that HBV infection and HCC prevalence show different correlations in various regions of the world indicates that there may be virusindependent phenomena for can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…[25] Since the majority (up to 90%) of the HBsAg is transcribed from integrated HBV DNA (iDNA) in patients with HBeAg-negative CHB [26][27][28] and iDNA is strongly correlated with HBsAg level, [29] perhaps the greater qHBsAg decline and lower end of follow-up qHBsAg have reduced transcriptional activity of iDNA, an important cause of HBV carcinogenesis by means of its production of viral oncogenic protein, for example, HBx. [30][31][32] In contrast, continued Nuc therapy can interrupt new HBV DNA integration but not inhibit transcription from iDNA. [28] Hence, finite therapy had lower HCC incidence than those continued therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Since the majority (up to 90%) of the HBsAg is transcribed from integrated HBV DNA (iDNA) in patients with HBeAg-negative CHB [26][27][28] and iDNA is strongly correlated with HBsAg level, [29] perhaps the greater qHBsAg decline and lower end of follow-up qHBsAg have reduced transcriptional activity of iDNA, an important cause of HBV carcinogenesis by means of its production of viral oncogenic protein, for example, HBx. [30][31][32] In contrast, continued Nuc therapy can interrupt new HBV DNA integration but not inhibit transcription from iDNA. [28] Hence, finite therapy had lower HCC incidence than those continued therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it was demonstrated that lower HBsAg level correlated with lower long-term HCC recurrence and longer survival in a study of 522 patients with HBV-HCC who had received curative resection and Nuc treatment 25 . Since the majority (up to 90%) of the HBsAg is transcribed from integrated HBV DNA (iDNA) in patients with HBeAg-negative CHB 26–28 and iDNA is strongly correlated with HBsAg level, 29 perhaps the greater qHBsAg decline and lower end of follow-up qHBsAg have reduced transcriptional activity of iDNA, an important cause of HBV carcinogenesis by means of its production of viral oncogenic protein, for example, HBx 30–32 . In contrast, continued Nuc therapy can interrupt new HBV DNA integration but not inhibit transcription from iDNA 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been suggested that alterations of hemostasis, particularly of platelets, could have a role in hepatocarcinogenesis [ 35 , 36 ]. Additional mechanisms that promote the induction of HCC in patients with HBV, HCV, and HBV-HDV infection are discussed below ( Table 1 ) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Viral-related Hepatic Carcinogenesismentioning
confidence: 99%
“…HBV has been demonstrated to as a common etiological factor for hepatocarcinogenesis worldwide ( Amaddeo et al, 2015 ; Arslan et al, 2021 ). Emerging studies have been indicated that the TRIM family not only contributed to the progression of HCC but also participated in the modulation of HBV infection ( Fan et al, 2019 ; Liu et al, 2020 ; Mu et al, 2020 ), while to date, the relationship of TRIM with HBV-associated hepatocarcinogenesis is not well investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the eastern Pacific region and Africa, the chronic infection of hepatitis B virus (HBV) is still a predominant risk factor for the initiation and development of hepatoma carcinoma (HCC) ( Geng et al, 2015 ; Jia et al, 2020 ; Arslan et al, 2021 ; Jiang Y. et al, 2021 ). The occurrence and progress of HCC have a close association with various cellular factors regulated by HBV.…”
Section: Introductionmentioning
confidence: 99%